Distinct clinical phenotypes in a family with a novel truncating MEN1 frameshift mutation - Christoph Welsch; Anna Katharina Flügel; Susanne Rondot; Egbert Schulze; Ishani Sircar; Judith Nußbaumer; Jörg Bojunga (BMC Endocrine Disorders, 2022)
Abstract Background MEN1 mutations can inactivate or disrupt menin function and are leading to multiple endocrine neoplasia type 1, a rare heritable tumor syndrome. Case presentation We report on a MEN1 family with a novel heterozygous germline mutation, c.674delG; p.Gly225Aspfs*56 in exon 4 of the MEN1 gene. Diagnosis and clinical phenotyping of MEN1 was established by laboratory tests, ultrasound, biopsy, MRI imaging and endosonography. The clinical course of the disease was followed in the index patient and her family members for eight years. The mutation was associated with distinct clinical phenotypes in the index patient and three family members harboring p.Gly225Aspfs*56. Family members affected showed primary hyperparathyroidism but variable patterns of associated endocrine tumors, adrenal cortical adenomas, prolactinoma, multifocal pancreatic neuroendocrine tumors, insulinoma and nonsecretory neuroendocrine tumors of the pancreas. The mutation c.674delG; p.Gly225Aspfs*56 leads to a frameshift from codon 225 with early truncation of the menin protein. In silico analysis predicts loss of multiple protein-menin interactions in p.Gly225Aspfs*56, potentially rendering menin insufficient to control cell division and replication. However, no aggressive neuroendocrine tumors were observed in the follow-up of this family. Conclusions We report a novel heterozygous MEN1 frameshift mutation, potentially causing (at least partial) inactivation of menin tumor suppression potential but lacking a genotype–phenotype correlation. Our study highlights the importance of personalized care with appropriate testing and counseling in MEN1 families.